Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am currently working with a class of functions, where every function looks like


where $v\in\mathbb{R}^n$ is an arbitrary vector, $A,B \in \mathbb{R}^{n\times n}$ are positive definite matrices and $x\in(0,1)$. Is there a straight forward way to prove, that $f(x)$ is convex on $(0,1)$?

share|cite|improve this question
up vote 2 down vote accepted

Proving that $f$ is a convex function of $x$ is the same as proving that $g(A) := v^T A^{-1}v$ is a convex function when defined on the domain of positive definite matrices. Fix positive definite matrices $A$ and $B$ and $\lambda\in [0,1]$. For any positive definite $C$ the Schur complement condition shows that \[ \begin{bmatrix} s & v^T \\ v & C\end{bmatrix} \] is positive semidefinite if and only if $s \geq v^TC^{-1}v$. The set of positive semidefinite matrices is convex, so the matrix \[ \lambda\begin{bmatrix}v^TA^{-1}v & v^T \\ v & A\end{bmatrix}+(1-\lambda)\begin{bmatrix}v^TB^{-1}v & v^T \\ v & B\end{bmatrix} = \begin{bmatrix}\lambda v^TA^{-1}v+(1-\lambda)v^TB^{-1}v & v^T \\ v & \lambda A + (1-\lambda)B\end{bmatrix} \] is positive semidefinite. The definition of $g$ and the Schur complement condition applied to the matrix on the right combine to give: \[ \lambda g(A) + (1-\lambda)g(B) = \lambda v^TA^{-1}v+(1-\lambda)v^TB^{-1}v \geq v^T(\lambda A + (1-\lambda)B)^{-1}v = g(\lambda A + (1-\lambda)B), \] so the function $g$ is convex.

share|cite|improve this answer

Fact If $X, Y$ are positive definite then $tX^{-1}+(1-t)Y^{-1}-(tX+(1-t)Y)^{-1}$ is positive semidefinite for $t\in (0,1)$. $X^{-1}$ is an operator convex function over the cone of positive definite matrices.

Now for any $\lambda\in(0,1)$, $f(\lambda x+(1-\lambda )y)=v^t\{[\lambda x+(1-\lambda )y]A+[1-\lambda x-(1-\lambda )y]B\}^{-1}v=v^t\{\lambda [xA+(1-x)B]+(1-\lambda)[yA+(1-y)B]\}^{-1}v\le \lambda f(x)+(1-\lambda)f(y)$.


share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.